Presternal gastric bypass for late postpneumonectomy esophagopleural fistula. - Dosios, T; Karavokyros, I; Felekouras, E; Sigala, F; Pikoulis, E; Spyrakos, S; Papalambros, E (Dis Esophagus, 2005)
SUMMARY: A 71-year-old diabetic patient underwent right pneumonectomy with wide mediastinal lymph node dissection for lung cancer (right upper lobe). Postoperatively he developed pleura empyema that was successfully treated - drainage and Eloesser window, followed by adjuvant radiotherapy. Two months later he developed an esophagopleural fistula. Due to the patient's physical condition primary repair of the esophageal rupture was considered a high-risk operation. Stenting was also considered as inappropriate due to the existing contamination. Bypassing with the use of the stomach as conduit was preferred due to its simplicity compared to the colon. In order to avoid mediastinum after the postradiation alterations and because of the Eloesser window we adopted a presternal subcutaneous position. Twenty-eight months after the by pass procedure the patient is in good health being able to eat and drink, has gained weight and shows no evidence of malignancy. Presternal gastric esophageal bypass has never been reported as a treatment for esophagopleural fistula. This case report indicates its possible successful use in this debilitating setting, although more experience is needed.
Keywords: Aged; Digestive System Surgical Procedures; Empyema, Pleural; Esophageal Fistula; Humans; Lung Neoplasms; Male; Pleural Diseases; Pneumonectomy; Radiotherapy; Stomach; Thoracic Surgical Procedures; Treatment Outcome